"Humic substances" measurement in sludge dissolved organic matter: A critical assessment of current methods. (April 2022) - Xiao, Keke; Horn, Harald; Abbt-Braun, Gudrun
Abstract: The role of humic substances (HS) during sludge treatment has been the focus in recent years. Quantification of HS in sludge dissolved organic matter (DOM) and the chemical and structural characterization of HS data are the prerequisite for understanding their role during different sludge treatment processes. Currently, a number of published articles inadequately acknowledge fundamental principles of analysis methods both in terms of experimental approach and data analysis. Therefore, a more comprehensive and detailed description of the experimental methods and the data analysis are needed. In this study, the current used methods for HS quantification in DOM of sludge had been tested for different calibration and sludge DOM samples. The results indicated that the current methods showed overestimated and contradictory results for HS quantification in sludge DOM. To be specific, using the modified Lowry method, different values were obtained depending on the humic acids used for calibration, and false negative results were observed for some sludge samples. By using the relative amount of HS (based on dissolved organic carbon (DOC)) to total sludge DOM (based on DOC), variations among the results of different analysis methods for the same sample were high. According to the calculated Bray-Curtis dissimilarity indexes, the results for HS quantification obtained by three-dimensional excitation emission matrix (3D-EEM), either with spectra analysis methods by peak picking, fluorescence region integration (both region volume and area integration), or PARAllel FACtor analysis showed higher degrees of dissimilarity to those quantified by size exclusion liquid chromatography or XAD-8 method. The selection of fluorescence regions for HS seemed to be the determining factor for overestimation obtained by the 3D-EEM technique. In future work, strategies, like a consistent terminology of HS, the use of an internal standard sample, and the related standardized operation for HS quantification in sludge DOM need to be established. Graphical abstract: Image 1 Highlights: Current methods showed contradictory results for HS quantification in sludge DOM. HS quantified by modified Lowry method varied depending on the chosen humic acids. HS obtained by 3D-EEM was more different to those quantified by LC-OCD or XAD-8.